2019
DOI: 10.1016/j.mib.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Control of bacterial colonization in the glands and crypts

Abstract: The epithelial cell layer of the major organs of the mammalian gastrointestinal (GI) tract is extensively invaginated into thousands of gland and crypt structures. These are lined by distinct sets of epithelial cells and may comprise discrete niches. The host maximizes the distance between the epithelial cell layer and GI-inhabiting microbes to limit inflammation, and these strategies also likely keep bacteria out of the glands and crypts. We discuss here the specific host processes that have been shown to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
(88 reference statements)
1
15
0
Order By: Relevance
“…Chemotaxis is cell movement in response to chemical cues employed by bacterial pathogens to migrate towards environments that are better for growth. Consequently contributes to these microorganisms to reach their preferred host niches, being an important subject of tissue tropism (Porter et al, 2011;Johnson and Ottemann, 2018;Matilla and Krell, 2018;Korolik, 2019;Yang and Ottemann, 2019). In the present study, we report the chemotactic behavior of reproductive pathogen C. fetus towards cervical mucus, bovine placenta and some reported substances and ion of bovine cervical mucus and bovine placenta, which brings an insight on the use of chemotaxis by C. fetus to reach their preferred colonization niches and the tissue tropism of this bacterium.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Chemotaxis is cell movement in response to chemical cues employed by bacterial pathogens to migrate towards environments that are better for growth. Consequently contributes to these microorganisms to reach their preferred host niches, being an important subject of tissue tropism (Porter et al, 2011;Johnson and Ottemann, 2018;Matilla and Krell, 2018;Korolik, 2019;Yang and Ottemann, 2019). In the present study, we report the chemotactic behavior of reproductive pathogen C. fetus towards cervical mucus, bovine placenta and some reported substances and ion of bovine cervical mucus and bovine placenta, which brings an insight on the use of chemotaxis by C. fetus to reach their preferred colonization niches and the tissue tropism of this bacterium.…”
Section: Discussionmentioning
confidence: 70%
“…Penetration and survive in mucus layer, guided by chemotaxis, is an essential step during the colonization of mucous surfaces by motile bacteria, favoring the establishment of bacterial populations in this environment (Alemka et al, 2012;Yang and Ottemann, 2019). In this context, attraction to mucus during the estrus, period in which the infection occurs, is a very relevant finding to the C. fetus pathogenesis in genital tract of the bovine female, since the bacterium is able to remain in the genital tract by successfully colonizing the mucus layer (Ware, 1980;Balzan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The corpus and antrum are distinct from each other in several ways. In each of these regions, the epithelium is highly invaginated into gastric glands that each contain stem cells (4,5). These stem cells give rise to a distinct set of epithelial cells in each area.…”
Section: Introductionmentioning
confidence: 99%
“… ABSTRACT Bacteria are efficient colonizers of a wide range of secluded micro-habitats, such as soil pores 1–3 , skin follicles 4 , dental cavities 5,6 or crypts in gut-like environments 7–9 . Although numerous factors promoting or obstructing stable colonization have been identified 10–14 , we currently lack systematic approaches to explore how population stability and resilience depend on the scale of the micro-habitat. Using a microfluidic device to grow bacteria in crypt-like incubation chambers of systematically varied lengths, we found that the incubation scale can sensitively tune bacterial colonization success and resistance against invaders.…”
mentioning
confidence: 99%
“…The ubiquity of micro-habitat associated stability and colonization resistance raises the question of whether these features generically emerge in confined spaces, for example soil pores 13–15 , skin follicles 4, 16 , or crypts and folds in gut-like environments 5,17,18 . Previous studies have identified biological features, such as suppressed biofilm growth or the expression of specific adhesion molecules, that promote stability in specific systemsb 1, 7, 19–21 . However, we currently lack systematic scale-dependent measurements to identify a generic mechanism of stability and resilience in micro-habitats, as well as a theory that could predict colonization success and tipping points.…”
mentioning
confidence: 99%